Xeena for schema: creating XML documents with a coordinated grammar tree. (11th November 2010) - Sifer, Mark; Dau, Frithjof; Hasan, Helen; Crawford, Kate; Peres, Yardena; Maarek, Yoelle
The vast heterogeneous network that is the World Wide Web requires common languages to facilitate the exchange and display of data and information in many forms. The Word Wide Web Consortium (W3C) developed the extensible markup language (XML) for this purpose. XML documents are produced automatically by applications or manually by users. When users do not produce documents regularly or when document languages are large and complex, manual editing can be a challenge. In these situations, better manual editing facilities that guide users and ease the burden of learning and recalling XML languages are needed. We present an XML editor design implemented in our Xeena for schema editor that addresses these needs. It is based on a new tree based grammar view that guides novice users and empowers experienced users to build XML documents. It lets users see and edit multiple levels of potential elements, unlike existing editors that present only one level of potential elements. We demonstrate its key features, present our grammar tree view design both informally and formally, and describe a user evaluation that supports the usability of our design.